Toward a structured concept for purpose-driven modeling of a digital shadow in manufacturing - Reichenstein, Tobias; Koustas, Spyridon Georg; Roßner, Alexander; Meiners, Moritz; Franke, Jörg (Procedia CIRP, 2023)
The growing relevance of Industry 4.0-related technologies and the transformation toward service-oriented business models in manufacturing requires relevant, high-qualitative data. The digital representation of operation and manufacturing under a specific purpose is called a digital shadow (DS). Although this purpose represents the decisive factor between different digital shadows, its systematic determination has been addressed insufficiently. Therefore, this paper presents a systematic, purpose-driven modeling approach for the digital shadow supporting manufacturing companies in developing a data basis for applications. This approach is applied to a crimping machine as an example and will be optimized in future evaluations.<br